Albania Early Childhood Development : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents an analysis of the early childhood development (ECD) programs and policies that affect young children in Albania and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER) - ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies, and interventions in Albania, along with regional and international comparisons.